Ismail Raji Al-Faruqi on Ummah and Its Relevance to Society 5.0 - Nabila Huringiin; Alia Safitri (Insaniyat : Journal of Islam and Humanities, 2023)
Society, which is a social structure, has its dynamics and can undergo significant changes. Society 5.0 is a new community concept promoted by Japan to be a solution to various social problems. Ismail Raji Al-Faruqi is one of the Muslim scholars who provide the concept of social order, one of which is the concept of the ummah. The purpose of this research is to find the relevance between Ummah and Society 5.0. The researcher uses a philosophical approach by using a qualitative research design or using a literature study by presenting a written presentation and the data that is analyzed and described. The results of this study are: the concept of ummah which is owned by Al-Faruqi and Society 5.0 is universalism which means that it is not particular and that all humans are the same, there are no differences in ethnicity, race, or nation. The concept of ummah Al-Faruqi and Society 5.0 has the concept of totalism which requires each individual to actualize divine values and will. The concept of ummah Al-Faruqi and Society 5.0 has the concept of independence where each individual has the freedom to will and will do what he does in realizing the values of life without any coercion. From these three concepts, the Islamic Society 5.0 concept was created which is characterized by a religious, intellectual, and observative society.